Job Search and the Duration of Layoff Unemployment - Pissarides, Christopher A. (Quarterly Journal of Economics, 1982)
This paper derives an optimal job-searching strategy for workers on layoff, and an optimal recall policy for firms, when each side anticipates the other side's actions correctly. It shows that workers search for an alternative job only if the probability of recall falls below a critical level, and that firms may recall before the recovery of demand, depending on the costs of laying off and hiring workers, and the probability of losing workers on layoff. Through the use of optimal job searching and recall policies, the paper derives expressions for the duration of layoff unemployment and discusses briefly their comparative-static properties.